Effect of complexing agent and deposition time on structural, morphological, optical and electrical properties of cuprous oxide thin films prepared by chemical bath deposition. (February 2022) - Reyes-Vallejo, Odín; Escorcia-García, J.; Sebastian, P.J.
Abstract: Cuprous oxide (Cu2 O) thin films were synthesized on corning glass substrates by chemical bath deposition. The influence of complexing agent and deposition time was investigated on the structural, morphological, optical and electrical properties of the thin films. It was found that the complexing agent triethanolamine (TEA) plays a key role not only promoting the adherence and crystallinity of Cu2 O, but also controlling the thickness by regulating the release of Cu + ions. The increase of complexing agent and long deposition times produce thicker films. It was found that thickness has a strong relation with preferential orientation. Thinner films (50–100 nm) present orientation along the (111) plane, which changes to the (200) plane as the thickness increases. Electrical conductivity decreases as the film becomes thicker, registering values of 10 1 (ohm*cm) −1 and 10 −4 (ohm*cm) −1 for 50 and 920 nm respectively. The structural defects, mainly Cu vacancies, are responsible for the variations in electrical properties and can be related to the Urbach energy (EU ) disorder. It was observed a decrease in EU when preferential orientation changes from (111) plane to (200) plane, which means less disorder and consequently less defects, which enhances the resistivity.